Debonding characterization of stiff film/compliant substrate systems based on the bilinear cohesive zone model. (15th April 2022) - Long, Hao; Liu, Yanwei; Wei, Yueguang
Highlights: A 2D theoretical model based on the bilinear CZM is proposed to characterize the debonding process of stiff film/compliant substrate systems. The results of the present model are verified by the previous experimental data and the FEM results. The present model can describe the full debonding process including the elastic, elastic-softening and elastic-softening-debonding stages. When the film modulus increases, the remote strain corresponding to the debonding initiation first decreases and then stabilizes at a certain value. Abstract: Interfacial debonding is one of the main failure modes of stiff film/compliant substrate systems, which are common in flexible electronics. In order to characterize their debonding process, we propose a theoretical model based on the bilinear cohesive zone model, where the stiff film acts like a membrane and the substrate is modeled by an elastic half-plane. The interfacial shear stress appears as a singular integral in the governing equations, and this term can be solved by expanding into the first-kind Chebyshev polynomials and further adopting the collocation method. The solutions of the present model are verified by the previous experimental data and the finite element analysis. The results indicate that the present model can not only capture the non-uniform deformation of the compliant substrate, but also describe the full debonding process including the elastic, elastic-softening and elastic-softening-debonding stages. Besides, the influences of film modulus, film thickness and interfacial properties on the debonding process are discussed. The present study can help us predict the debonding process of the stiff film/compliant substrate systems such as flexible electronics and guide the optimal design to prevent premature interfacial debonding.